2020
DOI: 10.1177/0009922820903037
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Loss in Children Due to Incorrect Early Diagnosis of Torsion

Abstract: Background. Testicular torsion is a common surgical emergency in children that requires a high index of suspicion, early diagnosis, and exploration. Most children present early to their primary pediatricians or physicians. The aim of this retrospective study is to determine the surgical outcome of testicular torsion with early as well as delayed presentation or referral at our pediatric surgical unit. Methods. Records of 50 patients who presented with testicular torsion at our pediatric surgical unit over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Our findings indicated that it was very important to strengthen the public awareness of TT, and effects must be conducted to continuously re-educate and update physicians working at primary and secondary healthcare units. This finding was consistent with two latest similar studies from India and Brazil [ 7 , 8 ], which indicated that improvement of accurate diagnosis of TT in primary and secondary healthcare units was greatly needed around the world.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings indicated that it was very important to strengthen the public awareness of TT, and effects must be conducted to continuously re-educate and update physicians working at primary and secondary healthcare units. This finding was consistent with two latest similar studies from India and Brazil [ 7 , 8 ], which indicated that improvement of accurate diagnosis of TT in primary and secondary healthcare units was greatly needed around the world.…”
Section: Discussionsupporting
confidence: 92%
“…A large number of studies reported that, worldwide, the delayed diagnosis and management of TT was quite common, and a relatively high proportion of TT patients proven to be delayed even in tertiary hospitals [ 7 , 8 ]. Aaron P. Bayne et al [ 1 ] and Christopher E. Bayne et al [ 9 ], in the United States, and Ekici et al [ 10 ] in Turkey, have investigated the clinical, socioeconomic and other factors associated with delayed management of TT, while there have no relevant reports among Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that MPV is increased in cases with testicular torsion and therefore it could be the indicator of testicular viability [ 15 ]. Several authors in their study have highlighted that despite of improved diagnostic facilities in case of confusion prompt scrotal exploration in the patient is warranted [ 16 - 19 ]. Chun et al in their study found the late presentation of acute scrotum leads to testicular loss.…”
Section: Discussionmentioning
confidence: 99%
“…40 Research has evaluated the predictors of TS in children with TT, 12,17 and we identified several risk factors associated with orchiectomy in children with TT in a multivariate analysis, including a longer interval between SP onset and PED arrival, 13,36,37 absent TUBF, 1,3,7,8,16,17,[31][32][33][34] interval between SP onset and surgery of more than 24 hours, 2,7,8,16 and a greater degree of TT. 17,18 Every patient with TTwho needed an orchiectomy on 1 testis had an orchiopexy on the other testis to prevent TT 20,21 and preserve fertility and endocrine function. Preventive orchiopexy on the other testis seemed to be effective in our series.…”
Section: Discussionmentioning
confidence: 99%